Detection and seroprevalence of morbillivirus and other paramyxoviruses in geriatric cats with and without evidence of azotemic chronic kidney disease. (23rd March 2018) - McCallum, Katie Elizabeth; Stubbs, Sam; Hope, Nicholas; Mickleburgh, Ian; Dight, Dave; Tiley, Laurence; Williams, Tim L.
Abstract : Background: Feline morbillivirus (FeMV) is associated with the presence of tubulo‐interstitial nephritis (TIN) in cats, however the seroprevalence of FeMV in the UK and the association between the presence of FeMV and renal azotemia is unknown Hypothesis/Objectives: To identify whether paramyxoviruses are present in urine samples of geriatric cats and to develop an assay to assess FeMV seroprevalence. To investigate the relationship between both urinary paramyxovirus (including FeMV) excretion and FeMV seroprevalence and azotemic chronic kidney disease (CKD). Animals: Seventy‐nine cats (40 for FeMV detection; 72 for seroprevalence). Methods: Retrospective cross‐sectional, case control study. Viral RNA was extracted from urine for RT‐PCR. PCR products were sequenced for virus identification and comparison. The FeMV N protein gene was cloned and partially purified for use as an antigen to screen cat sera for anti‐FeMV antibodies by Western Blot. Results: Feline morbillivirus RNA from five distinct morbilliviruses were identified. Detection was not significantly different between azotemic CKD (1/16) and nonazotemic groups (4/24; P = .36). Three distinct, non‐FeMV paramyxoviruses were present in the nonazotemic group but their absence from the azotemic group was not statistically significant ( P = .15). 6/14 (43%) azotemic cats and 40/55 (73%) nonazotemic cats were seropositive ( P = .06). Conclusions and Clinical Importance: Feline morbillivirus was detected in cats in the UK for the First time. However, there was no association between virus prevalence or seropositivity and azotemic CKD. These data do not support the hypothesis that FeMV infection is associated with the development of azotemic CKD in cats in the UK.